Corporations and Environmental Crimes: A Legal Analysis of Criminal Liability in Indonesia - Agustinus, Akwila; Arifin, Ridwan (Semarang State University Undergraduate Law and Society Review, 2025)
Environmental damage caused by corporations in Indonesia poses a serious threat to ecological sustainability and community welfare. This paper aims to analyze the legal framework and implementation of corporate criminal liability in environmental crimes. The main issue discussed is the ineffectiveness of law enforcement in holding corporations accountable despite their significant role in causing environmental damage. Using a normative juridical method, this research examines laws, doctrines, court decisions, and relevant legal literature. This study identifies several legal theories used to establish corporate liability, including the theory of identification, strict liability, and vicarious liability. The research findings reveal that although the Indonesian legal system, particularly Law No. 32 of 2009 and the new Criminal Code (Law No. 1 of 2023), recognizes corporations as criminal law subjects, their practical enforcement remains weak. The main challenges include corporate structural complexity, difficulties in proving mens rea, regulatory ambiguity, and political or economic influences. This study concludes that more effective enforcement mechanisms are needed, involving not only criminal sanctions but also remedial actions such as environmental restoration and corporate accountability. Strengthening institutional capacity, inter-agency coordination, and public participation are crucial steps toward improving environmental justice. This research underscores the urgency of comprehensive legal reform to ensure that corporations can be held criminally liable and contribute to sustainable environmental governance.